Elasto-capillarity in insect fibrillar adhesion - Gernay, Sophie (J R Soc Interface, 2016)
The manipulation of microscopic objects is challenging because of high adhesion forces, which render macroscopic gripping strategies unsuitable. Adhesive footpads of climbing insects could reveal principles relevant for micro-grippers, as they are able to attach and detach rapidly during locomotion. However, the underlying mechanisms are still not fully understood. In this work, we characterize the geometry and contact formation of the adhesive setae of dock beetles (Gastrophysa viridula) by interference reflection microscopy. We compare our experimental results to the model of an elastic beam loaded with capillary forces. Fitting the model to experimental data yielded not only estimates for seta adhesion and compliance in agreement with previous direct measurements, but also previously unknown parameters such as the volume of the fluid meniscus and the bending stiffness of the tip. In addition to confirming the primary role of surface tension for insect adhesion, our investigation reveals marked differences in geometry and compliance between the three main kinds of seta tips in leaf beetles.